Streptococcus agalactiae caused a Secondary Infection in Sexually Transmitted Infections : Case Report - Nurpagino, Bombong; Apriyanto, Muchammad; Susetiati, Devi Artami; Nuryastuti, Titik (Ahmad Dahlan Medical Journal, 2024)
Streptococcus agalactiae is a gram-positive coccus bacterium that is rarely reported to cause genital infections in males. This study discusses case of a young man with lesions on the genital as a secondary infection caused by Streprococcus agalactiae. A 25-year-old man came to the dermatology and venereology clinic of Dr. Sardjito General Hospital, complaining of a wound on the penis that had not healed in the last 3 months ago, The patient has a history of having sex with men without using a condom and frequently changing partners. The patient was known to be infected with HIV (Human Immunodeficiency Virus) and the results of the IgG HSV-2 (Herpes Simplex Virus-2) serological examination were positive. The results of microbiological examination of the wound bed swab sample showed the growth of Streptococcus agalactiae. Previously the patient received antiretroviral therapy, clindamycin oral, and erythromycin cream. The wound on the penis got better, but before the wound completely recovered, the patient did not visit anymore. Streptococcus agalactiae secondary infection in cases of sexually transmitted infections is a rare case. In this case, the finding of Streptococcus agalactiae can be considered as a pathogen. In cases of sexually transmitted infections with sores on the genital, a microbiological examination is recommended to determine the causative microorganism, and an antibiotic sensitivity test to determine the therapy.